CUSTOMS PRIVILEGES: MECHANISM OF PROVIDING AND TERMINATION - Davydovska, H. I.; Kulchytska, S. M. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
Purpose. Investigation of the organizational and legal mechanism of customs privileges and tariff preferences, consisting of such elements as subjects of installation, object of providing, legal grounds and conditions for the provision and cancellation. Methodology of research. Theoretical and methodological basis of the research is based on the scientific works of local and foreign authors concerning the research of the essence of customs privileges, Internet resources. In the process of research general and special methods are used. The main method used for launching this investigation is the method of research of normative legal sources, and customs code in particular. On the basis of the logical and semantic method, the organizational-legal mechanism of customs privileges is investigated. Results. Summing up the study of the organizational and legal mechanism of customs privileges, as well as the conditions and grounds for getting customs privileges, it should be noted that from the point of view of the form and content, this mechanism needs a substantial revision of all its levels. There is no unambiguous and clear regulation of the issue regarding the authority of a state body or competence of an official representative to establish, change or cancel customs privileges. The view is expressed about the need for amendments to the relevant normative acts, which determine the subject of customs privileges provision, providing exclusive right to this higher authority of the legislative body with further specification of the mechanism of this procedure by the executive authorities. As a result, differences in the evaluation criteria exist in their content of customs preferences: customs privileges viewed primarily in terms of social outcomes, tariff preferences observed according to their economic effect. Innovation. The concept of customs privileges and tariff preferences as separate types of legal privileges in the field of customs relations achieved further development; formulated the principles of providing customs privileges and tariff preferences. Practical value. The obtained results create the preconditions for further in-depth study of the theory and practice of customs privileges, tariff preferences in the field of customs relations, as well as provide the opportunity to apply them for further scientific developments in the customs field, legislative and normative activity of state authorities.